EUS-guided fiducial marker placement for radiotherapy in rectal cancer: feasibility of two placement strategies and four fiducial types - Rigter, Lisanne S.; Rijkmans, Eva C.; Inderson, Akin; van den Ende, Roy P.J.; Kerkhof, Ellen M.; Ketelaars, Martijn; van Dieren, Jolanda; Veenendaal, Roeland A.; van Triest, Baukelien; Marijnen, Corrie A.M.; van der Heide, Uulke A.; van Leerdam, Monique E. (Endoscopy International Open, 2019)
Background and study aims To facilitate image guidance during radiotherapy of rectal cancer, we investigated the feasibility of fiducial marker placement. This study aimed to evaluate technical success rate and safety of two endoscopic ultrasound (EUS)-guided placement strategies and four fiducial types for rectal cancer patients.Patients and methods This prospective multicenter study included 20 participants who were scheduled to undergo rectal cancer treatment with neoadjuvant short-course radiotherapy or chemoradiation. EUS-guided endoscopy was used for fiducial placement at the tumor site (n = 10) or in the mesorectal fat and in the tumor (n = 10). Four fiducial types were used (Visicoil 0.75 mm, Visicoil 0.50 mm, Cook, Gold Anchor). The endpoints were technical success rate and retention of fiducials, the latter of which was evaluated on cone-beam computed tomography scans during the first five radiotherapy fractions.Results A total of 64 fiducials were placed in 20 patients. For each fiducial type, at least three fiducials were successfully placed in all patients. Technical failure consisted of fiducial blockage within the needle (n = 2) and ejection of two preloaded fiducials at once (n = 4). No serious adverse events were reported. In three patients, one of the fiducials was misplaced without clinical consequences; two in the prostate and one in the intraperitoneal cavity. After a median time of 17 days after placement (range 7 – 47 days), a total of 42/64 (66 %) fiducials were still present (24/44 intratumoral vs. 18/20 mesorectal fiducials, P = 0.009). Conclusions Placement of fiducials in rectal cancer patients is feasible, however, retention rates for intratumoral fiducials were lower (55 %) than for mesorectal fiducials (90 %).